Alcohol Abuse and Cardiac Disease - Whitman, Isaac R; Agarwal, Vratika; Nah, Gregory; Dukes, Jonathan W; Vittinghoff, Eric; Dewland, Thomas A; Marcus, Gregory M (Journal of the American College of Cardiology, 2017)
Understanding the relationship between alcohol abuse, a common and theoretically modifiable condition, and the most common cause of death in the world, cardiovascular disease, may inform potential prevention strategies. The study sought to investigate the associations among alcohol abuse and atrial fibrillation (AF), myocardial infarction (MI), and congestive heart failure (CHF). Using the Healthcare Cost and Utilization Project database, we performed a longitudinal analysis of California residents ≥21 years of age who received ambulatory surgery, emergency, or inpatient medical care in California between 2005 and 2009. We determined the risk of an alcohol abuse diagnosis on incident AF, MI, and CHF. Patient characteristics modifying the associations and population-attributable risks were determined. Among 14,727,591 patients, 268,084 (1.8%) had alcohol abuse. After multivariable adjustment, alcohol abuse was associated with an increased risk of incident AF (hazard ratio [HR]: 2.14; 95% confidence interval [CI]: 2.08 to 2.19; p < 0.0001), MI (HR: 1.45; 95% CI: 1.40 to 1.51; p < 0.0001), and CHF (HR: 2.34; 95% CI: 2.29 to 2.39; p < 0.0001). In interaction analyses, individuals without conventional risk factors for cardiovascular disease exhibited a disproportionately enhanced risk of each outcome. The population-attributable risk of alcohol abuse on each outcome was of similar magnitude to other well-recognized modifiable risk factors. Alcohol abuse increased the risk of AF, MI, and CHF to a similar degree as other well-established risk factors. Those without traditional cardiovascular risk factors are disproportionately prone to these cardiac diseases in the setting of alcohol abuse. Thus, efforts to mitigate alcohol abuse might result in meaningful reductions of cardiovascular disease.